Impact of environmental contamination on a fractional model of Methicillin-Resistant Staphylococcus Aureus (MRSA) infection in hospitals - Öztürk, Bahar Acay (My University, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is an endemic pathogen in many hospital settings, posing an economic burden to patients, hospitals, and society. In this study, we aim to control the persistence and spread of MRSA in the population with a mathematical model created by employing the non-local Caputo derivative. Moreover, the effect of environmental contamination, which is an important parameter in the clinical epidemiology of healthcare-associated infection, is observed. On the other hand, the baseline reproduction number is calculated to achieve the desired results. Numerical analysis is then performed to observe the model's asymptotic behavior. Additionally, real data collected from Beijing Tongren Hospital is utilized in numerical simulations of the model to obtain information about the process of the disease. Consequently, it is shown that the results obtained by employing the advantages of the Caputo operator can be used as a guide for the development of control methods, such as paying attention to hand hygiene of healthcare workers, increasing the disinfection of the environment and reducing the risk of contamination between the patients-healthcare professionals and environment.
Keywords: Mathematical biology; Healthcare-associated infection; Caputo fractional operator; fractional modeling; non-local derivative